Chaos-control and Locking in a Dual-ring Er-doped Fiber Laser by Adjusting Loss - Yan, Senlin (Recent Advances in Electrical & Electronic Engineering, 2018)
Background: We studied how to control a dual-ring Er-doped fiber laser by shifting the laser loss, pressuring the chaotic behavior of the laser to a periodic state or multi-periodic states. Methods: We present a model of single-parameter control of the laser. When a periodic signal adjusts the loss of one ring, the dynamic behavior of the laser can stabilize into period-one states and the dualring output variation locks at the adjusting signal frequency where two rings can emit cyclic pulses. We find such a control-locking-frequency region, indicating that the chaotic dual-ring Er-doped fiber laser can be effectively controlled. We also find a locking-half-frequency region, in which the dual-ring output locks at a half-frequency of the adjusting signal. When the loss shifts between two values, the laser can be deduced to multi-periodic states or be pressured into two single-period states where two rings cam emit cyclic pulses. We also find that the controlled laser can exhibit dual dynamics, in which the dual-ring shows two dynamic behaviors, such as, one ring showing a period-two state, while the other ring shows a period-three state or stabilizes to a period-one state. Results: Our results indicate that the chaos- of a dual-ring erbium-doped fiber laser can be controlled.
Keywords: chaos